Personalisation and its Influence on Identities, Behaviour and Social Values - van der Hof, Simone; Prins, Corien (Profiling the European Citizen, 2008)
New ICTs support new ways of tailoring services to the individual needs and desires of customers. Increasingly, what is called personalisation of services is implemented particularly in Internet-based e-commerce applications but other kinds of technologies and services, such as location-based services, RFID, smartcards and biometrics are expected to follow closely and offer even better opportunities for personalised services. The growing popularity of personalisation requires an exploration of the broader and fundamental implications of this phenomenon. Issues related to the categorisation of people, the creation of identities, the (re)structuring of behaviour and the shaping of the overall movement of information and expression within society need consideration when implementing such techniques in organisational (e.g., e-Government) and business processes. More specifically, this chapter deals with privacy, transparency and the quality of personalisation processes, as well as inclusion, exclusion and control. It is argued that the phenomenon of personalisation must be deliberated in light of the broader developments in the area of ubiquitous computing.